The γ decay of the Hoyle and higher excitation energy states of 12C. (December 2020) - Cardella, G.; Favela, F.; Martorana, N.S.; Acosta, L.; Auditore, L.; Camaiani, A.; Filippo, E. De; Gelli, N.; Geraci, E.; Gnoffo, B.; Guazzoni, C.; Marìn-Làmbarri, J.; et al.
Abstract: The 0 2 + Hoyle state and few other excited levels of 12 C are fundamental for the production of carbon in the universe. In particular, the γ decay branching ratio is of utmost importance, being the only way to produce a carbon at the ground state. For the purpose to precisely investigate the decay mechanism of such states we conducted an experiment, at Laboratori Nazionali del Sud-Istituto Nazionale di Fisica Nucleare (INFN-LNS), using the reaction α + 12 C at 64 MeV. We used the 4 π CHIMERA detector to detect both α and γ 12 C decay channels. Details of the experiment and preliminary results are discussed in the paper.